Caracterização fenotípica de isolados de Pyrenophora tritici-repentis e reação de genótipos de trigo para mancha-amarela-da-folha - Bertagnolli, Victória Vieira (2018)
The tan spot disease, caused by Pyrenophora tritici-repentis (Ptr), is one of the most importantfoliar diseases of wheat crop, causing losses and damages in different wheat production regions of the world. Considering that there is a lack of information on the races structure in Brazil and on sources of resistance in Brazilian genotypes, this work characterized phenotypically and genotypically Ptr isolates and thus described wheat genotypes with resistance to the Brazilian Ptrraces and the host-selective toxins (HST) Ptr ToxA and Ptr ToxB. The results were presented and discussed separately in this document, in two chapters. Chapter 1: Phenotypical and genotypical characterization of Pyrenophora tritici-repentis races in Brazil. Isolates from wheat leaves and seeds from different wheat productions regions of the country were inoculated on the differential set of wheat genotypes, including Glenlea, 6B662, 6B365, Salamouni, ND -495 and BR 34. The symptoms produced on the leaves were observed and classified in necrosis, chlorosis or resistance response, and thus the races were designated by the phenotypical characterization. In regard to the genotypical characterization, this was accomplished by the amplification of the genes responsible for the production of the HST Ptr ToxA and Ptr ToxB by Polymerase Chain Reaction. The phenotypical characterization indicates Ptr 2 race as predominant in Brazil, followed by race 1, and the genotypical characterization confirms presence of ToxA and absence of ToxB by Brazilian isolates, corroborating the phenotypical characterization of this study. Chapter 2: Resistance to Pyrenophora tritici-repentis in common wheat. 38 wheat genotypes were analyzed for the components of resistance: relative infection efficiency, final number of lesions, final lesion length, lesion expansion and lesion type. All components were evaluated with inoculations of races 1 and 2 of Ptr. In addition, the genotypes were evaluated for sensitivity to toxins Ptr ToxA and Ptr ToxB by the technique of infiltration of toxins in leaves with needleless syringe. The experiments were performed in greenhouse and growth chambers. Non-parametric statistical tests were performed to compare cultivars between races, cultivars within races, and to compare toxin infiltration with resistance components, using p -value <0.050 in all tests. Genotypes resistant to Ptr races 1 and 2 were observed, as well as the predominance of genotypes insensitive to Ptr ToxA and Ptr ToxB. FPS Virtude, BRS Parrudo, LG Cromo, Quartzo, and TBIO Sossego are adapted Brazilian genotypes, statistically superior to the others for genetic resistance to tan spot, being able to be used strategically in studies of resistance in wheat breeding programs and in crops with prediction of environmental conditions and records favorable to the disease.